Extraction of movement related oscillatory changes from electroencephallogram with application to brain-computer interface : : doctoral thesis - Jerbić, Ana Branka (A.B. Jerbić ; Fakultet elektrotehnike i računarstva, 2015)
SUMMARY: A brain computer interface (BCI) is a technology that decodes a user's intent from brain activity. Obtained information can be used to control devices in the user's environment. In this thesis, changes in sensorimotor rhythms (SMR) during motor imagery (MI) are extracted from electroencephalogram (EEG). These changes are reflected in amplitude attenuation (event related desynchronization) or enhancement (event related synchronization) of SMRs in certain brain regions. Extracted features are classified to left hand, right hand and feet MI, which is possible since MI of different parts of the body results in spatially distinct activation of motor cortex. The brain is a complex organ and interindividual differences in EEG are considerable. In this thesis, parameters influencing the classification accuracy of MI based BCI are identified and analyzed. It is demonstrated that for maximal classification accuracy a MI based BCI has to be custom designed. SMR changes can be detected using time frequency (TF) methods of analysis. A TF method called the Hilbert Huang transform (HHT) was utilized to facilitate the extraction of SMRs, while a well established band power (BP) method served as a reference method for comparison purposes. The HHT was successful in the extraction of SMR changes, but did not outperform the simple BP method. However, the HHT revealed the existence of a phenomenon that, to the author's knowledge, has not been reported previously in the literature. It concerns the increase of frequency in the MI period on the contralateral side of the brain in those intrinsic mode functions, obtained using the HHT, which contain SMRs. -